Money is more than memory - Maria Bigoni; Gabriele Camera; Marco Casari (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Impersonal exchange is the hallmark of an advanced society. One key institution for impersonal exchange is money, which economic theory considers just a primitive arrangement for monitoring past conduct in society. If so, then a public record of past actions - or memory - supersedes the function performed by money. This intriguing theoretical postulate remains untested. In an experiment, we show that the suggested functional equality between money and memory does not translate into an empirical equivalence. Monetary systems perform a richer set of functions than just revealing past behaviors, which proves to be crucial in promoting large-scale cooperation.
urn:nbn:de:hebis:30:3-356109
Keywords: C70; C90; D03; E02; 330; cooperation; intertemporal trade; experiments; social norms; social dilemmas